Equipment of transport infrastructure and intensity of tourist traffic in Polish voivodeships in 2015-2019 - Pilichowska, Paulina; Glądała, Aleksandra (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
Tourist traffic, an appropriate level of tourism development and tourist values are the three most important elements that must exist in a given area in order to be able to say that it performs a tourist function. Transport accessibility is defined as one of the factors influencing tourist attractiveness of the region. Among the numerous methods of its measurement, accessibility measured in this study is distinguished by infrastructure equipment. The aim of the study is to organise Polish voivodeships in terms of the intensity of tourist traffic and the availability of transport infrastructure equipment, to assess their diversity and changes over time. The study covered 16 voivodeships of Poland. The time scope of the study covers the years 2015 and 2019. The analysis was carried out on the basis of statistical information from the database of the Central Statistical Office. The analysis showed that the Polish voivodeships are highly diversified both in terms of the intensity of tourist traffic and the equipment of the transport infrastructure. The hypothesis that the Polish voivodeships, which are characterised by the highest degree of intensity of tourist traffic, have the most developed transport infrastructure, while those which, due to the intensity of tourist traffic, have taken the last positions in the ranking, are characterised by a low level of transport infrastructure equipment has not been confirmed.